A multi-modal biofeedback protocol to demonstrate physiological manifestations of psychological stress and introduce heart rate variability biofeedback stress management. Issue 4 (2nd October 2018) - Gross, Mike J.; Bringer, Joy D.; Kilduff, Liam P.; Cook, Christian J.; Hall, Ross; Shearer, David A.
Abstract: Physiological monitoring solutions and biofeedback technologies allow sport psychology practitioners to demonstrate physiological changes due to psychological stress, and provide their clients with an enhanced awareness of their stress response. These technologies can also provide evidence for the efficacy of stress management techniques, whether cognitive or physiological in nature. In this article, we present a protocol that uses multiple physiological signals to demonstrate how psychological stress can manifest in the body, and then evidence heart rate variability biofeedback as a stress management technique. Using insights from applied consultations, we focus on the delivery of the protocol through phases of baseline resting measures, stressor tasks, and post-stressor recovery. This article provides an accessible use of physiological monitoring and biofeedback technologies in sport psychology practice, so that practitioners may adopt and adapt this protocol for their purposes and available equipment.